The debate in bioethics - Sgreccia, Elio (Medicina e Morale, 1989)
We begin from this issue a new column which, in a more or less constant way, will collect the opinions of readers and those who are experts in the subject, regarding the numerous problems that are emerging in Bioethics, as much in the doctrinal and foundational sphere as in that of the special part and clinical ethics. We therefore invite those who wish to participate in this debate to send their contributionswhich, for reasons of space, we ask be contained in one to two typed folders per space. These contributions may be published by the Editorial Board, which also reserves the right to condense them if they are too long or more than one on the same topic.